Estudo experimental, numérico e analítico de nova interface para uma ligação por aderência aço - concreto - Costa, Lays Raianne Azevedo da (2020)
Construction systems favorizing the execution of faster civil engineering works have been prioritized. Given this, precast elements can contribute to reducing the delay observed in traditional civil construction works. Precast elements can be produced outside the construction site, which leads to greater control of the production process and the choice of the constituent materials of the system. As well as the precast elements, the steel- structures can also be produced outside the construction site and then transported and assembled with welding; therefore, the combination of the two solutions can result in a structure with more quality and economy. However, in order to obtain a monolithic steel-concrete behavior, the need for the presence of connectors is evident. Most of the connectors already studied are not completely adapted to the reality of precast systems and, the use of connections by adherence, whose resistance is due to friction between interfaces, can be an alternative to this problem. The study of the connection by adherence is based on the investigation of the behavior of the interfaces, subject to confinement, and shear stresses. Interfaces are the object resulting from the contact between two materials. Some types of steel-concrete interfaces in connections by adherence have already been studied, but the development of new possibilities for interfaces may represent an advance in this field of research. This research aimed to study experimentally, numerically, and analytically the behavior of the steel-concrete interface composed by “Checkered” steel plates. For that, a systematic review, characterization tests, direct shear tests and Pull Out tests, numerical simulation using the ABAQUS® computational package and calibration of laws to describe the behavior of the interface were performed. The results showed that the resistance of the interfaces is proportional to the confinement stress and the resistance of the cementitious materials in the interface. Both the numerical simulation and the calibrated analytical laws showed a good correlation with the results obtained experimentally.